Impact of Comorbidity on Length of Stay of Hospitalized Pneumonia in Children - Nur Mala Il A'la; Adi Utomo Suardi; Dewi Kartika Turbawati (Faculty of Medicine Universitas Padjadjaran, 2017)
Background: The incidence of pneumonia in children under-five in West Java is high. The average length of stay (LOS) often exceeds the standards set by the Indonesia-Disease Related Group (INA-DRG) because of the comorbidities. It can cause financial loss for the hospital. This study was conducted to analyze the impact of comorbidity on LOS.Methods: Data was collected from medical records of 296 hospitalized pneumonia under-five children in the Department of Child Health Dr. Hasan Sadikin General Hospital Bandung in the period from January–December 2012 that consisted of patient’s identity, LOS, primary diagnosis, and comorbid diagnosis. Data was selected through inclusion and exclusion criteria and statistically analyzed using the chi-square and Spearman correlation test.Results: Out of 218 subjects, those who had major comorbidities and minor comorbidities was 79 (36.2%) and 39 (17.9%), respectively. The average LOS of those who had major and minor comorbidities was 8.33±8.252 days and 5.95±3.554 days, respectively. Congenital heart disease had the highest and most significant Risk Ratio (RR) with average LOS was 8.00±4.889 days with RR: 1.895 (95% CI:1.339–2.682, p=0.001).Conclusions: Subjects have higher average LOS than the LOS set by the INA-DRG. Congenital heart disease is the most common comorbidity and has the highest and the most significant risk ratio. [AMJ.2017;4(1):42–6]DOI: 10.15850/amj.v4n1.1019